2016
DOI: 10.3390/f7080176
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Dynamics during Foliar Litter Decomposition in an Alpine Forest Meta-Ecosystem

Abstract: Abstract:To investigate the dynamics and relative drivers of cellulose degradation during litter decomposition, a field experiment was conducted in three individual ecosystems (i.e., forest floor, stream, and riparian zone) of an alpine forest meta-ecosystem on the eastern Tibetan Plateau. Four litter species (i.e., willow: Salix paraplesia, azalea: Rhododendron lapponicum, cypress: Sabina saltuaria, and larch: Larix mastersiana) that had varying initial litter chemical traits were placed separately in litterb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This pattern was even more obvious during the early decomposition stages, when substantial amounts of water‐soluble substances (e.g., carbohydrates, phenolics and free amino acids) can lost as a result of the higher leaching and flushing effects found in streams (Berg & McClaugherty, ). Recent studies found that recalcitrant components, such as lignin, can also be substantially degraded during early decomposition stages (Yue, Peng, et al., ; Yue, Wu, et al., ). As lignin degradation is controlled by the availability of easily decomposable carbon sources (KlotzbĂŒcher, Kaiser, Guggenberger, Gatzek, & Kalbitz, ), the rapid decline of these labile C compounds in streams may also accompany higher lignin degradation rates.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was even more obvious during the early decomposition stages, when substantial amounts of water‐soluble substances (e.g., carbohydrates, phenolics and free amino acids) can lost as a result of the higher leaching and flushing effects found in streams (Berg & McClaugherty, ). Recent studies found that recalcitrant components, such as lignin, can also be substantially degraded during early decomposition stages (Yue, Peng, et al., ; Yue, Wu, et al., ). As lignin degradation is controlled by the availability of easily decomposable carbon sources (KlotzbĂŒcher, Kaiser, Guggenberger, Gatzek, & Kalbitz, ), the rapid decline of these labile C compounds in streams may also accompany higher lignin degradation rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, a debate has also arisen regarding lignin and cellulose loss. Recent studies declared that a greater loss rate can also be found during the early phase of decomposition due to microenvironmental factors, such as hydrology [10], snow cover [4,5], and solar radiation [11], which can influence the degradation process directly or indirectly. However, the effects of species mixing on lignin and cellulose degradation have seldom been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that carbon accumulates during the litter decomposition process, possibly because the decomposition rate of material with other elemental concentrations of the litter is greater than the carbon release rate at this phase. It is accompanied by the accumulation of recalcitrant material (such as lignin and condensed phenolic compounds) that is difficult to decompose [68,69], leading to an increase in the proportion of carbon in the total weight of the litter, manifested as litter carbon concentration increase and carbon accumulation. Therefore, as mentioned above, typhoons drive material cycle processes in subtropical urban forests by altering the production and quality of litter, increasing the rate of mass loss and carbon release from litter.…”
Section: Effects Of Typhoon Disturbance On Abnormal Litter Carbon Rel...mentioning
confidence: 99%